Lone fighters: Intraparty competition, interparty competition, and candidates' vote seeking efforts in open-ballot PR elections. (September 2015) - Selb, Peter; Lutz, Georg
Abstract: In their seminal paper, Carey and Shugart (1995) argue that electoral rules predetermine whether election campaigns are predominantly characterized by competition between parties, or among candidates within parties. In particular, electoral systems that provide weak party control over ballot access, that allow voters to express a preference vote for individual candidates, and that select candidates on the basis of the votes they earn individually are supposed to offer strong incentives for candidates to cultivate a personal vote. In this paper, we investigate Carey and Shugart's original claims about the instrumental motivations of candidates in open-ballot proportional representation (PR) elections using survey data and election statistics from the 2007 Swiss National Council elections. As opposed to previous work, we develop and employ more direct and valid measures of intra- and interparty incentives to wage personal campaigns. Our empirical results suggest that the candidates' campaign focus and expenditures are closely linked to intraparty competition, but not interparty competition. Previously used proxies of intraparty competition, such as district magnitude or the number of candidates on a party list (or ratios thereof), turn out to be but remotely related to the candidates' campaign behavior. Highlights: We investigate Carey and Shugart's (1995) original claims about the instrumental motivations of candidates in open-ballot PR elections. We develop appropriate measures of intra- and interparty competition. Using survey data and election statistics from the 2007 Swiss National Council elections, we demonstrate that the candidates' campaigning behavior is strongly related to intraparty (not interparty) competition.